Stretched film and method for producing same
By using a high-density high-density polyethylene and ethylene-vinyl alcohol copolymer combination, combined with a specific stretching treatment process, the problem of difficult to achieve water vapor barrier properties and heat resistance in the packaging film is solved, and excellent water vapor barrier properties, heat resistance and oxygen barrier properties are achieved.
Patent Information
- Application Number
- CN202380053190.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-05
- Filing Date
- 2023-06-09
- Publication Date
- 2025-02-28
AI Technical Summary
In the existing packaging film, the ethylene-vinyl alcohol copolymer has oxygen barrier properties but does not have water vapor barrier properties, and the oxygen barrier properties are reduced in high humidity environments. At the same time, the water vapor barrier properties of the base material layer are insufficient and there is a problem of heat shrinkage, making it difficult to achieve water vapor barrier properties and heat resistance at the same time.
High-density polyethylene with a density of 0.950 g/cm3 or more is used as the first base layer, and ethylene-vinyl alcohol copolymer is used as the barrier layer, and water vapor transmission and heat shrinkage are controlled through a specific stretching treatment process to improve the water vapor barrier and heat resistance of the film.
A stretched film with excellent water vapor barrier properties, heat resistance and oxygen barrier properties is realized, and the problems of insufficient water vapor barrier properties and thermal shrinkage in the prior art are solved.
Smart Images

Figure CN119546462A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a stretch film for use as a packaging film or the like and a method for producing the same. Background Art
[0002] Conventionally, as packaging films used for packaging bags and the like, for example, a laminated body is used in which a base film formed of a resin material and a sealing film formed of a material different from the resin material forming the base film are laminated.
[0003] Here, there is a demand for reducing the environmental load of plastics as a whole, and packaging films are also required to be recyclable. However, in the case of a laminated body made by stacking films formed from the above-mentioned different types of materials, it is difficult to separate the materials, thus causing a problem of difficulty in recycling.
[0004] Therefore, in recent years, the trend of making packaging films from a single raw material has been increasing. As resins used for packaging films that have been made from a single material, for example, polyethylene, polypropylene, polyethylene terephthalate, etc. can be listed. Among them, polyethylene is the most commonly used raw material in existing packaging films, and is particularly required to be made from a single material. However, polyethylene monomers have poor gas barrier properties (oxygen barrier properties) and cannot be set with a shelf life like existing laminated films. In addition, when the contents are cosmetics such as detergents or shampoos, odor leakage will occur, which is a problem.
[0005] Therefore, as a method for making it have gas barrier properties, for example, a stretched film including a substrate layer with polyethylene resin as the main component and a barrier layer with ethylene-vinyl alcohol copolymer (EVOH) as the main component has appeared. In addition, there is also the following record: With the above structure, it is possible to form a barrier layer with ethylene-vinyl alcohol copolymer as the main component by using a T-die method (a type of extrusion molding method), inflation molding, etc., just like the existing laminated film, so that a stretched film with oxygen barrier properties can be manufactured without increasing manufacturing equipment and manufacturing processes. In addition, there is also the following record: By forming other layers (substrate layer, sealing film layer) with polyethylene, the content of ethylene-vinyl alcohol copolymer is reduced, so that the entire laminate can be regarded as a single raw material of polyethylene, which can improve recycling and reusability (for example, refer to Patent Document 1).
[0006] Patent Document 1: Japanese Patent Publication No. 2021-154656 Summary of the invention
[0007] -Technical problem to be solved by the invention-
[0008] Here, although ethylene-vinyl alcohol copolymer has oxygen barrier properties, it does not have water vapor barrier properties. In addition, it is also known that the oxygen barrier properties of ethylene-vinyl alcohol copolymer decrease in a high humidity environment. As for the stretched film described in the above-mentioned Patent Document 1, the resin disclosed as forming the substrate layer is 0.925 g / cm 3 However, the water vapor barrier property of the substrate layer is insufficient. In addition, the heat shrinkage rate at 100°C is large, and the substrate layer shrinks during the heat sealing process during bag making, resulting in wrinkles and poor appearance. As a result, it is difficult to achieve both water vapor barrier property and heat resistance.
[0009] Therefore, the present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a stretched film having excellent water vapor barrier properties, excellent heat resistance, and also excellent oxygen barrier properties.
[0010] -Technical solutions to solve technical problems-
[0011] In order to achieve the above-mentioned object, the stretched film of the present invention comprises at least a first substrate layer and a barrier layer, wherein: the first substrate layer has a density of 0.950 g / cm 3 The above polyethylene is the main component, the barrier layer is ethylene-vinyl alcohol copolymer as the main component, and the water vapor transmission rate is 3.5g / m 2 · days or less, and the heat shrinkage when heated at 100°C for 10 minutes in the stretching direction of the film is 5% or less.
[0012] In addition, the method for producing a stretched film of the present invention is characterized in that: it includes at least a step of preparing an original film and a step of stretching the original film, wherein the original film includes at least a film having a density of 0.950 g / cm 3 The base layer mainly composed of polyethylene and the barrier layer mainly composed of ethylene-vinyl alcohol copolymer are stretched at a stretching temperature of 80° C. to less than 130° C. and a stretching ratio of 5 to 10.
[0013] - Effects of the Invention -
[0014] According to the present invention, it is possible to provide a stretched film having excellent water vapor barrier properties, excellent heat resistance, and also excellent oxygen barrier properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 is a cross-sectional view for explaining a laminated body produced by using a stretched film according to a first embodiment of the present invention;
[0016] Figure 2 is a plan view for explaining a laminated body produced by using a stretched film according to a first embodiment of the present invention;
[0017] Figure 3 is a cross-sectional view for explaining a laminated body produced by using a stretched film according to a second embodiment of the present invention;
[0018] Figure 4 It is a plan view for explaining a laminated body produced using a stretched film according to a second embodiment of the present invention. DETAILED DESCRIPTION
[0019] The stretched film of the present invention will be described in detail below. It should be noted that the present invention is not limited to the following embodiments, and can be applied with appropriate modifications within the scope of the present invention.
[0020] (First Embodiment)
[0021] Figure 1 It is a cross-sectional view for explaining a laminated body produced using the stretched film according to the first embodiment of the present invention.
[0022] The laminate 1 includes a stretched film 10 and a sealing film 2. The stretched film 10 is composed of a substrate layer 3 and a barrier layer 5. The substrate layer 3 has polyethylene as a main component; the barrier layer 5 has ethylene-vinyl alcohol copolymer as a main component and is laminated on the substrate layer 3 via an adhesive layer 4. The sealing film 2 is laminated on the barrier layer 5 of the stretched film 10.
[0023] <Sealing film>
[0024] From the viewpoint of single material, the sealing film 2 is preferably made of a polyethylene resin, more specifically, high-density polyethylene (HDPE), medium-density polyethylene (MDPE), low-density polyethylene (LDPE), and linear low-density polyethylene (LLDPE).
[0025] It should be noted that from the viewpoint of improving heat sealing properties, in order to form a melting point difference between the sealing film 2 and the substrate layer 3, the polyethylene resin of the sealing film 2 is preferably a low-density polyethylene (LDPE) or linear low-density polyethylene (LLDPE) having a lower melting point than the substrate layer 3.
[0026] The content of polyethylene in the sealing film 2 is preferably 70% or more, more preferably 90% or more, further preferably 95% or more, and most preferably 100%.
[0027] The thickness of the sealing film 2 is preferably 20 μm to 200 μm, and more preferably 30 μm to 150 μm.
[0028] Furthermore, the sealing film 2 may contain other components other than the above-mentioned polyethylene-based resin within a range that does not impair the characteristics of the sealing film 2 .
[0029] Other ingredients include olefin resins, amide anti-blocking agents (such as stearic acid amide), plasticizers, ultraviolet absorbers, antioxidants, weather stabilizers, antistatic agents, colorants, antifogging agents, metal soaps, waxes, mildewproofing agents, antibacterial agents, nucleating agents, flame retardants, lubricants, and the like.
[0030] <Base layer (first base layer)>
[0031] The base layer 3 is a layer that imparts water vapor barrier properties to the stretched film 10 and is formed with high-density polyethylene (HDPE) as a main component. In the present invention, the density of the high-density polyethylene is 0.950 g / cm 3 Above. At a density of 0.950g / cm 3 In the above case, since the crystallinity of polyethylene is improved, the water vapor barrier property can be improved.
[0032] In order to further improve the water vapor barrier properties, the density of the high-density polyethylene is preferably higher than 0.955 g / cm 3 , more preferably 0.962 g / cm 3 More preferably, 0.970 g / cm 3 above.
[0033] In addition, the melt mass flow rate (MFR) of the high-density polyethylene is preferably 0.01 to 3.00 g / 10 min, more preferably 0.02 to 2.50 g / 10 min, and further preferably 0.1 to 2.00 g / 10 min. The reasons are as follows: when the melt mass flow rate (MFR) is 0.01 g / 10 min or more, it can be formed using a general-purpose extruder without using special equipment; when the melt mass flow rate (MFR) is 3.00 g / 10 min or less, it can have sufficient film strength.
[0034] It should be noted that the above-mentioned melt mass flow rate can be obtained by measuring in accordance with the provisions of Japanese Industrial Standard JIS K7210:1999.
[0035] In order to obtain excellent water vapor barrier properties, the content of the high-density polyethylene relative to the entire substrate layer 3 is preferably 90% by mass or more, more preferably 95% by mass or more, based on 100% by mass of the substrate layer.
[0036] As mentioned above, by using a density of 0.950 g / cm 3 The above high-density polyethylene is used as the resin forming the substrate layer 3, and the water vapor permeability of the stretched film 10 reaches 3.5 g / m 2·day or less, it is possible to provide the stretched film 10 having excellent water vapor barrier properties.
[0037] It should be noted that from the viewpoint of improving water vapor barrier properties, the water vapor permeability of the stretched film 10 is preferably 3.0 g / m 2 ·Day or less, more preferably 2.5g / m 2 ·Day or less.
[0038] The “water vapor transmission rate” referred to herein refers to a value measured using a water vapor transmission rate tester in accordance with Japanese Industrial Standard JIS K 7129-1 in an atmosphere of a temperature of 40° C. and a humidity of 90%.
[0039] Furthermore, the base material layer 3 may contain other components other than the high-density polyethylene as long as the stretchability of the film is not impaired.
[0040] Other ingredients include olefin resins, amide anti-blocking agents (such as stearic acid amide), plasticizers, ultraviolet absorbers, antioxidants, weather stabilizers, antistatic agents, colorants, antifogging agents, metal soaps, waxes, mildewproofing agents, antibacterial agents, nucleating agents, flame retardants, lubricants, and the like.
[0041] <Barrier layer>
[0042] The barrier layer 5 is a layer for imparting oxygen barrier properties to the stretched film 10 and is formed of ethylene-vinyl alcohol copolymer (EVOH) as a main component.
[0043] In addition, the ethylene-vinyl alcohol copolymer used for the barrier layer 5 is not particularly limited, and the ethylene content (content of ethylene units) in the ethylene-vinyl alcohol copolymer is preferably 30 to 40 mol%, more preferably 32 to 38 mol%, relative to the total amount (100 mol%) of all monomer units constituting the ethylene-vinyl alcohol copolymer. The reason is as follows: when the ethylene content is less than 30 mol%, the processability of the barrier film may be reduced, and when the ethylene content is more than 40 mol%, the oxygen barrier property may become insufficient.
[0044] In order to obtain excellent oxygen barrier properties, the content of the ethylene-vinyl alcohol copolymer relative to the entire barrier layer 5 is preferably 90% by mass or more, more preferably 95% by mass or more, based on 100% by mass of the barrier layer.
[0045] As described above, since ethylene-vinyl alcohol copolymer is used as the resin forming the barrier layer 5, the oxygen permeability of the stretched film 10 reaches 10 cc / m 2 ·day or less, it is possible to provide the stretched film 10 having excellent oxygen barrier properties.
[0046] It should be noted that from the viewpoint of improving oxygen barrier properties, the oxygen permeability of the stretched film 10 is preferably 5.0 cc / m 2 ·Day or less, more preferably 3.0cc / m 2 ·Day or less, more preferably 1.5cc / m 2 ·Day or less.
[0047] The “oxygen permeability” referred to herein refers to a value measured using an oxygen permeability tester in accordance with Japanese Industrial Standard JIS K 7126-1 in an atmosphere of a temperature of 23° C. and a humidity of 0%.
[0048] In addition, similarly to the substrate layer 3 , the barrier layer 5 may contain other components (eg, other components in the substrate layer 3 ) in addition to the ethylene-vinyl alcohol copolymer as long as the stretchability of the film is not impaired.
[0049] <Adhesive layer (first adhesive layer)>
[0050] The adhesive layer 4 is a layer for bonding the base layer 3 and the barrier layer 5 , and is mainly composed of a material having excellent bonding properties between the base layer 3 and the barrier layer 5 , such as modified polyolefin.
[0051] Examples of the modified polyolefin include modified polyethylene and modified polypropylene. More specifically, acid-modified polyethylene and acid-modified polypropylene are included. In addition, from the perspective of single material, modified polyethylene is preferred.
[0052] <Method for producing laminate>
[0053] Next, a method for producing a laminated body using the stretched film of the present embodiment will be described in detail.
[0054] First, resin compositions for the substrate layer, the barrier layer, and the adhesive layer are prepared.
[0055] Next, using an extruder including a T-die, the resin compositions of the respective layers are co-extruded at a predetermined temperature to obtain an original film before stretching having a substrate layer 3, an adhesive layer 4 provided on the surface of the substrate layer 3, and a barrier layer 5 provided on the surface of the adhesive layer 4.
[0056] Then, the original film is subjected to uniaxial stretching or biaxial stretching to produce Figure 1-2The stretched film 10 is shown. The stretched film 10 is specifically as follows: the substrate layer 3, the adhesive layer 4 and the barrier layer 5 are stacked in this order, and the adhesive layer 4 is provided between the substrate layer 3 and the barrier layer 5. It should be noted that the stretching method is not particularly limited, and examples thereof include roller stretching, calendar stretching, and the like.
[0057] In addition, the above uniaxial stretching treatment is Figure 2 The stretching treatment is performed along the mechanical axis (length) direction of the film (hereinafter referred to as "MD") and along the direction orthogonal to the MD (hereinafter referred to as "TD") as shown. It should be noted that biaxial stretching treatment can also be performed along both the MD and TD directions.
[0058] The stretching temperature of the uniaxial stretching treatment is 80° C. to less than 130° C., preferably 100° C. to 120° C. The reason is as follows: if it is less than 80° C., the film may have white spots; if it is 130° C. or more, the film may melt and break.
[0059] In addition, the stretching ratio of the uniaxial stretching treatment is 5 times or more and 10 times or less. The reasons are as follows: when the stretching ratio is less than 5 times, there will be a residual unstretched portion, so there is a situation where the tensile strength and transparency are reduced; when the stretching ratio is greater than 10 times, there is a situation where the film breaks. In addition, from the viewpoint of improving tensile strength and transparency and preventing film breakage, the stretching ratio is preferably 6 times or more and 8 times or less.
[0060] Therefore, the stretched film 10 manufactured by the stretching process described above has a haze of 20% or less, and thus can obtain excellent transparency.
[0061] In addition, from the viewpoint of further improving transparency, the haze of the stretched film 10 is preferably 15% or less, more preferably 10% or less, and even more preferably 7% or less.
[0062] In addition, the "haze" mentioned here is an index of haze measured according to Japanese Industrial Standard JIS K 7361.
[0063] The stretched film 10 of the present embodiment has a heat shrinkage of 5% or less in the stretching direction of the film when heated at 100°C for 10 minutes. When the heat shrinkage is 5% or less, the dimensional stability during heat treatment is high, and thus a stretched film having excellent heat resistance can be provided.
[0064] In addition, when the density of the high-density polyethylene which is the main component of the base material layer 3 increases, the melting point of the high-density polyethylene increases, and thus an increase in the heat shrinkage rate can be suppressed.
[0065] From the viewpoint of improving heat resistance, the heat shrinkage rate of the stretched film 10 is preferably 3% or less, and more preferably 1% or less.
[0066] In addition, the above-mentioned "heat shrinkage ratio" can be obtained by the method described in Examples mentioned later.
[0067] In addition, for the stretched film 10 of the present embodiment, the tensile stress at break along at least one of the MD and TD directions is preferably 100 MPa or more. If the tensile stress at break is 100 MPa or more, sufficient strength is obtained, so that during subsequent printing, lamination, and other processes, a stretched film 10 having stable dimensions during transportation and excellent transportability can be provided.
[0068] In addition, from the viewpoint of improving transparency by stretching, the tensile breaking stress of the stretched film 10 is preferably 200 MPa or more, and more preferably 240 MPa or more.
[0069] The above-mentioned "tensile breaking stress" refers to the stress measured in accordance with Japanese Industrial Standard JIS K 7127.
[0070] In addition, the thickness of the original film before stretching is preferably 50 to 400 μm, more preferably 80 to 300 μm. If the thickness of the original film is 50 μm or more, the strength that can withstand the stress during stretching can be obtained; if the thickness of the original film is 400 μm or less, sufficient transparency can be obtained after stretching.
[0071] In addition, the thickness of the substrate layer after the stretching treatment is preferably 10 to 40 μm, and more preferably 15 to 30 μm. If the thickness of the substrate layer 3 after the stretching treatment is 10 μm or more, sufficient strength and water vapor barrier properties can be obtained as a substrate film. In addition, if the thickness of the substrate layer after the stretching treatment is 40 μm or less, sufficient transparency can be obtained.
[0072] In addition, the thickness of the barrier layer 5 after the stretching treatment is preferably 2 to 10 μm, and more preferably 3 to 6 μm. If the thickness of the barrier layer 5 after the stretching treatment is 2 μm or more, sufficient strength and sufficient oxygen barrier properties can be obtained as a barrier film; if the thickness of the barrier layer 5 after the stretching treatment is 10 μm or less, a film with excellent recyclability can be obtained.
[0073] The thickness of the adhesive layer 4 after the stretching treatment is not particularly limited, but is preferably 0.3 to 2 μm, and more preferably 0.5 to 1 μm.
[0074] From the viewpoint of improving recyclability, the content of polyethylene relative to the entire stretched film 10 is preferably 70% by mass or more, more preferably 75% by mass or more, based on 100% by mass of the stretched film.
[0075] By the above method, in the present embodiment, it is possible to obtain the stretched film 10 having excellent water vapor barrier properties, excellent heat resistance, and also excellent oxygen barrier properties.
[0076] Next, raw materials containing polyethylene resins such as the above-mentioned high-density polyethylene (HDPE), medium-density polyethylene (MDPE), low-density polyethylene (LDPE) and linear low-density polyethylene (LLDPE) are prepared, and the above-mentioned raw materials are melt-extruded using an extruder including a T-die head to form a film to produce a sealing film 2.
[0077] Then, for example, the barrier layer 5 of the stretched film 10 and the sealing film 2 are laminated with an adhesive to produce Figure 1 The laminate 1 is shown.
[0078] Here, according to the guidelines established by the European Economic Community, i.e., the Circular Economy for Flexible Packaging (CEFLEX), when the content of polyethylene in the entire laminate is 90% by mass or more and ethylene-vinyl alcohol copolymer, adhesive, etc. are used, if the content of each of ethylene-vinyl alcohol copolymer, adhesive, etc. in the entire laminate is less than 5% by mass, the laminate is considered to have achieved a single material. Therefore, by making the stretch film 10 have the above-mentioned structure, after the sealing film 2 has been laminated on the stretch film 10, a laminate 1 that is considered to have achieved a single material can be provided.
[0079] (Second Embodiment)
[0080] Next, a second embodiment of the present invention will be described. It should be noted that the same components as those of the first embodiment are denoted by the same reference numerals and their description will be omitted.
[0081] Figure 3 2 is a cross-sectional view showing a stretched film according to a second embodiment of the present invention. Figure 3 As shown, the stretched film 11 in this embodiment is characterized in that, in addition to the substrate layer 3 described in the above-mentioned first embodiment and the barrier layer 5 stacked on the substrate layer 3 via the adhesive layer 4, it also includes a substrate layer 7 stacked on the barrier layer 5 via the adhesive layer 6, and the substrate layer is two layers.
[0082] It should be noted that if Figure 3As shown, the laminated body 20 includes the above-mentioned stretched film 11 and the sealing film 2 laminated on the base material layer 7 of the stretched film 11 .
[0083] <Base layer (second base layer)>
[0084] Like the substrate layer 3, the substrate layer 7 is formed mainly of high-density polyethylene, and the density of the high-density polyethylene is 0.950 g / cm 3 Therefore, the crystallinity of polyethylene is improved. Therefore, like the base material layer 3, the water vapor barrier property can be improved.
[0085] It should be noted that, from the viewpoint of further improving the water vapor barrier property, the density of the high-density polyethylene is preferably higher than 0.955 g / cm 3 , more preferably 0.962 g / cm 3 More preferably, 0.970 g / cm 3 above.
[0086] In addition, from the viewpoint of being able to be molded using a general-purpose extruder and having sufficient film strength, the melt mass flow rate (MFR) of the high-density polyethylene is preferably 0.01 to 3.00 g / 10 min, more preferably 0.02 to 2.50 g / 10 min, and further preferably 0.1 to 2.00 g / 10 min, as with the substrate layer 3.
[0087] In addition, like the substrate layer 3, from the viewpoint of obtaining excellent water vapor barrier properties, the content of high-density polyethylene relative to the entire substrate layer 7 is preferably 90 mass % or more in 100 mass % of the substrate layer, and more preferably 95 mass % or more in 100 mass % of the substrate layer.
[0088] It should be noted that, like the stretched film 10, the water vapor permeability of the stretched film 11 is 3.5 g / m 2 ·day or less, but from the viewpoint of improving water vapor barrier properties, the water vapor permeability of the stretched film 11 is preferably 3.0 g / m 2 ·Day or less, more preferably 2.5g / m 2 ·Day or less.
[0089] In addition, similarly to the base layer 3 , the base layer 7 may contain other components than the high-density polyethylene as long as the stretchability of the film is not impaired.
[0090] <Adhesive layer (second adhesive layer)>
[0091] As with the adhesive layer 4 described above, the adhesive layer 6 may contain a modified polyolefin as a main component.
[0092] <Method for producing laminate>
[0093] Next, a method for producing a laminated body using the stretched film of the present embodiment will be described in detail.
[0094] The laminate 20 of this embodiment is manufactured as described below, similarly to the case of the first embodiment. First, resin compositions for the substrate layer, barrier layer, and adhesive layer are prepared, and then, using an extruder including a T-die, the resin compositions of each layer are co-extruded at a predetermined temperature to obtain an original film before stretching, which includes a substrate layer 3, an adhesive layer 4 provided on the surface of the substrate layer 3, a barrier layer 5 provided on the surface of the adhesive layer 4, an adhesive layer 6 provided on the surface of the barrier layer 5, and a substrate layer 7 provided on the surface of the adhesive layer 6.
[0095] Then, the original film is uniaxially stretched to produce Figure 3-4 The stretched film 11 shown in the figure is specifically as follows: the substrate layer 3, the adhesive layer 4, the barrier layer 5, the adhesive layer 6 and the substrate layer 7 are stacked in this order, the adhesive layer 4 is provided between the substrate layer 3 and the barrier layer 5, and the adhesive layer 6 is provided between the barrier layer 5 and the substrate layer 7. It should be noted that the stretching method is not particularly limited, and examples thereof include roller stretching, calendar stretching, and the like.
[0096] In addition, the above uniaxial stretching treatment is Figure 4 The stretching treatment shown is performed in any one direction of MD and TD. It should be noted that biaxial stretching treatment may also be performed in both directions of MD and TD.
[0097] In addition, as in the first embodiment described above, the stretching temperature of the uniaxial stretching treatment is greater than 80°C and less than 130°C, preferably greater than 100°C and less than 120°C, and the stretching ratio of the uniaxial stretching treatment is greater than 5 times and less than 10 times, preferably greater than 6 times and less than 8 times.
[0098] Also, similar to the stretched film 10 described above, the stretched film 11 produced by the stretching process described above has a haze of 20% or less, and thus can have excellent transparency.
[0099] In addition, from the viewpoint of further improving transparency, the haze of the stretched film 11 is preferably 15% or less, more preferably 10% or less, and even more preferably 7% or less.
[0100] In addition, the stretched film 11 of this embodiment has a heat shrinkage of 5% or less when heated at 100° C. for 10 minutes in the stretching direction of the film, similarly to the stretched film 10. If the heat shrinkage is 5% or less, the dimensional stability during heat treatment is high, and thus the stretched film 11 having excellent heat resistance can be provided.
[0101] As with the above-mentioned base layer 3 , when the density of the high-density polyethylene which is the main component of the base layer 7 is increased, the melting point of the high-density polyethylene is increased, and thus an increase in the heat shrinkage rate can be suppressed.
[0102] From the viewpoint of improving heat resistance, the heat shrinkage rate of the stretched film 11 is preferably 3% or less, and more preferably 1% or less.
[0103] In addition, the stretched film 11 of this embodiment preferably has a tensile stress of 100 MPa or more in at least one of MD and TD, as in the above-mentioned stretched film 10. If the tensile stress of 100 MPa or more is sufficient, the stretched film 11 can be provided with a stable dimension and excellent transportability during transportation when performing subsequent printing, lamination and other processes.
[0104] In addition, from the viewpoint of improving transparency, the tensile breaking stress of the stretched film 11 is preferably 200 MPa or more, and more preferably 240 MPa or more.
[0105] In addition, the thickness of the original film before the stretching treatment, the thickness of the barrier layer 5 after the stretching treatment, and the thickness of the adhesive layers 4 and 6 after the stretching treatment are preferably the same as those in the first embodiment. In addition, the thickness of the substrate layer 3 and the substrate layer 7 are each preferably 5 to 20 μm, and more preferably 7 to 15 μm.
[0106] From the viewpoint of improving recyclability, the content of polyethylene relative to the entire stretched film 11 is preferably 70% by mass or more, more preferably 75% by mass or more, based on 100% by mass of the stretched film.
[0107] By the above method, in the present embodiment, it is possible to obtain the stretched film 11 which has excellent water vapor barrier properties, excellent heat resistance, and also excellent oxygen barrier properties.
[0108] Next, raw materials containing polyethylene resins such as the above-mentioned high-density polyethylene (HDPE), medium-density polyethylene (MDPE), low-density polyethylene (LDPE) and linear low-density polyethylene (LLDPE) are prepared, and the above-mentioned raw materials are melt-extruded using an extruder including a T-die head to form a film to produce a sealing film 2.
[0109] Then, for example, the base material layer 7 of the stretched film 11 and the sealing film 2 are laminated with an adhesive to produce Figure 3 The laminated body 20 shown. Also, similarly to the first embodiment, by making the stretched film 11 have the above-mentioned structure, after the sealing film 2 is laminated on the stretched film 10, the laminated body 20 which is regarded as having achieved a single material can be provided.
[0110] [Example]
[0111] The present invention will be described below based on the embodiments. It should be noted that the present invention is not limited to these embodiments, and these embodiments can be deformed and changed according to the purpose of the present invention, and these deformations and changes shall not be excluded from the scope of the present invention.
[0112] The materials used to make the stretch film are as follows.
[0113] (1) HDPE1: High-density polyethylene (density: 0.971 g / cm 3 , melting point: 134°C, MFR: 1.2g / 10min, manufactured by The Dow Chemical Company, USA, trade name: ELITE AT6900)
[0114] (2) HDPE2: High-density polyethylene (density: 0.962 g / cm 3 、Melting point: 133℃、MFR: 0.24g / 10min、Made by Prime Polymer Co., Ltd.、Trade name: HI-ZEX 520MB)
[0115] (3) HDPE3: High-density polyethylene (density: 0.958 g / cm 3 、Melting point: 133℃、MFR: 0.98g / 10min、Made by Prime Polymer Co., Ltd.、Trade name: HI-ZEX 3600F)
[0116] (4) HDPE4: High-density polyethylene (density: 0.950 g / cm 3 、Melting point: 133℃、MFR: 0.3g / 10min、Made by Prime Polymer Co., Ltd.、Trade name: HI-ZEX 6800S)
[0117] (5) HDPE5: High-density polyethylene (density: 0.943 g / cm 3 、Melting point: 126℃、MFR: 0.24g / 10min、Made by Prime Polymer Co., Ltd.、Trade name: HI-ZEX 5100E)
[0118] (6) EVOH 1: Ethylene-vinyl alcohol copolymer (density: 1.16 g / cm 3, melting point: 183°C, MFR: 2.0 g / 10 min, ethylene content: 32 mol%, manufactured by Kuraray Co., Ltd., trade name: EVAL SP482B).
[0119] (7) EVOH2: ethylene-vinyl alcohol copolymer (density: 1.18 g / cm 3 、Melting point: 183℃、MFR:
[0120] 1.7 g / 10 min, ethylene content: 32 mol%, manufactured by Kuraray Co., Ltd., trade name: EVAL J171B)
[0121] (8) Binder: modified polyethylene (density: 0.91 g / cm 3 、Melting point: 120℃、MFR: 2.3g / 10min、Made by Mitsui Chemicals, Inc.、Trade name: ADMER NF587)
[0122] (Example 1)
[0123] <Production of Stretch Film>
[0124] First, high-density polyethylene, ethylene-vinyl alcohol copolymer, and modified polyethylene shown in Table 1 were prepared.
[0125] Next, the prepared resin was co-extruded at 200° C. using an extruder including a T-die (manufactured by Labtech Co., Ltd.) to form a film having a first substrate layer, a first adhesive layer provided on the surface of the first substrate layer, a barrier layer provided on the surface of the first adhesive layer, a second adhesive layer provided on the surface of the barrier layer, and a second substrate layer provided on the surface of the second adhesive layer, and the film was wound up using a winding roller to obtain an original film before stretching having a thickness shown in Table 1.
[0126] Then, the original film was subjected to uniaxial stretching treatment in MD under the conditions of the stretching temperature and stretching ratio shown in Table 1, thereby stretching the original film to produce a stretched film having a thickness shown in Table 1.
[0127] <Calculation of polyethylene content>
[0128] Next, calculate the density [g / cm 3 ] and the thickness [μm] of each layer shown in Table 1 to find the weight per unit area of each layer [g / cm 2 ], and the content [mass %] of polyethylene relative to the entire produced stretched film was calculated. The above results are shown in Table 1.
[0129] It should be noted that, in this embodiment, the sum of the weight per unit area of the first substrate layer and the second substrate layer formed of high-density polyethylene is 0.002709 [g / cm 2 ], the weight per unit area of the barrier layer formed by the ethylene-vinyl alcohol copolymer is 0.000661 [g / cm 2 ], the sum of the weight per unit area of the first adhesive layer and the second adhesive layer formed of modified polyethylene is 0.000145 [g / cm 2 ] Therefore, the content [mass %] of polyethylene relative to the entire stretched film produced is 0.002709 / (0.002709+0.000661+0.000145)=77.1 mass %.
[0130] <Measurement of water vapor transmission rate>
[0131] Next, the water vapor transmission rate (g / m2) of the prepared stretched film was measured using a water vapor transmission rate tester (manufactured by SYSTEC Illinois, trade name: Water Vapor Transmission Rate Analyzer Lyssy L80-6000) in accordance with Japanese Industrial Standard JIS K 7129-1 at a temperature of 40°C and a humidity of 90%. 2 The above results are shown in Table 1.
[0132] <Measurement of oxygen transmission rate>
[0133] Next, the oxygen permeability of the prepared stretched film was measured using a gas permeability tester (manufactured by GTR TEC Co., Ltd., trade name: GTR-10XACT) in accordance with Japanese Industrial Standard JIS K 7126-1 at a temperature of 23°C and a humidity of 0%. 2 The above results are shown in Table 1.
[0134] <Measurement of haze and total light transmittance>
[0135] The haze [%] of the polyethylene in the visible light region (range of 360 to 750 nm) was measured as an index of the haze of the produced stretched film using a spectrophotometer (manufactured by Suga Testing Instruments Co., Ltd., Japan, trade name: haze meter HZ-V3) in accordance with Japanese Industrial Standard JIS K 7361 as an index of the haze of the produced stretched film. In addition, the total light transmittance [%] of the produced stretched film was measured in accordance with Japanese Industrial Standard JIS K 7361-1. The above results are shown in Table 1.
[0136] <Measurement of tensile breaking stress>
[0137] According to Japanese Industrial Standard JIS K 7127, the tensile stress at break [MPa] of the produced stretched film was measured. More specifically, a test film of dumbbell type No. 3 was prepared, and a tensile test was performed using a tensile testing machine (manufactured by Shimadzu Corporation, trade name: Autograph AG-5000A) at a temperature of 25°C and a tensile speed of 100 mm / min, and the tensile stress at break [MPa] in MD and TD was measured. The above results are shown in Table 1.
[0138] <Calculation of thermal shrinkage>
[0139] A sample of a specified size (7 cm × 7 cm) was cut from the produced stretched film, and a marking line parallel to each side and 5 cm long and orthogonal to each other was marked on the inner side of the sample 1 cm away from each side. The sample was placed in an oven at 100°C, heated for 10 minutes, then taken out and cooled to room temperature. Then, the distance between the marking lines in the stretching direction (i.e., MD) was measured for the sample after heat treatment, and the heat shrinkage [%] was calculated from the change in the distance between the marking lines before and after heating in the stretching direction using the following formula (1), and the heat shrinkage was used as an indicator of heat resistance. The above results are shown in Table 1.
[0140] Thermal shrinkage in the stretching direction [%] = [(distance between markings before heating - distance between markings after heating) / distance between markings before heating] × 100 (1)
[0141] (Examples 2 to 7, Comparative Examples 1 to 4)
[0142] Except for changing the composition of the stretched film (i.e., high-density polyethylene, ethylene-vinyl alcohol copolymer and modified polyethylene) and the conditions of the uniaxial stretching treatment to those shown in Table 1, other aspects are the same as the above-mentioned Example 1. Under such conditions, the original film having the thickness shown in Table 1 is stretched to produce a stretched film.
[0143] Then, the polyethylene content was calculated, the water vapor transmission rate was measured, the oxygen transmission rate was measured, the haze and total light transmittance were measured, the tensile breaking stress was measured, and the heat shrinkage was calculated in the same manner as in Example 1. The above results are shown in Tables 1 and 2.
[0144] It should be noted that in Comparative Example 4, since the stretching temperature during the film formation by uniaxial stretching was 130° C. or higher (130° C.), the stretched film melted and broke. Therefore, in Comparative Example 4, it was impossible to calculate the polyethylene content, measure the water vapor permeability, measure the oxygen permeability, measure the haze and measure the total light transmittance, measure the tensile breaking stress, and calculate the heat shrinkage.
[0145] (Comparative Example 5)
[0146] <Production of Stretch Film>
[0147] First, high-density polyethylene was prepared as shown in Table 2. Then, the prepared high-density polyethylene was melt-extruded (extrusion temperature: 200° C.) using an extruder including a T-die (manufactured by Nagata Seisakusho Co., Ltd.) to form a film, and the film was wound up with a winding roll to obtain an original film before stretching having a thickness shown in Table 2.
[0148] Then, the original film was uniaxially stretched in MD under the conditions of the stretching temperature and stretching ratio shown in Table 2 to produce a stretched film (polyethylene film) made of high-density polyethylene having a thickness shown in Table 2.
[0149] Then, the polyethylene content was calculated, the water vapor transmission rate was measured, the oxygen transmission rate was measured, the haze and total light transmittance were measured, the tensile breaking stress was measured, and the heat shrinkage was calculated in the same manner as in Example 1. The above results are shown in Table 1.
[0150] [Table 1]
[0151]
[0152] [Table 2]
[0153]
[0154] As shown in Table 1, for the stretched films of Examples 1 to 7, since the density of polyethylene is 0.950 g / cm 3 Above, water vapor transmission rate is 3.5g / m 2 · Day or less, oxygen permeability is 10cc / m 2 ·day or less, it can be seen that the water vapor barrier and oxygen barrier properties are excellent. In addition, since the heat shrinkage rate when heated at 100°C for 10 minutes in the stretching direction of the film is 5% or less, it can be seen that the dimensional stability during heat treatment is high and the heat resistance is excellent. In addition, since the haze (HAZE) is 20% or less, it can be seen that the transparency is excellent.
[0155] On the other hand, as shown in Table 2, in the stretched films of Comparative Examples 1 and 2, since the density of polyethylene is less than 0.950 g / cm 3 Therefore, it can be known that the water vapor transmission rate is greater than 3.5g / m 2 ·day, lacks water vapor barrier properties. In addition, since the density of polyethylene is less than 0.950g / cm 3 Polyethylene has a low melting point, so it can be seen that the thermal shrinkage rate is greater than 5% and lacks heat resistance.
[0156] In addition, as for the stretched film of Comparative Example 3, since the stretching temperature is low, the heat fixing effect cannot be obtained, so it can be seen that the heat shrinkage rate is greater than 5%, and the heat resistance is poor. In addition, since the stretching temperature is lower than 80°C, it can be seen that the film has white spots and the haze becomes much greater than 20%, and the transparency is poor.
[0157] In addition, since the stretched film of Comparative Example 5 does not have a barrier layer formed of an ethylene-vinyl alcohol copolymer, it is found that the oxygen permeability is lower than 20 cc / m 2 · Day is much larger and lacks oxygen barrier properties.
[0158] - Industrial Applicability -
[0159] In summary, the present invention is suitable for a stretch film used for packaging film or the like and a method for producing the same.
[0160] - Explanation of symbols -
[0161] 1 Laminated body
[0162] 2 Sealing film
[0163] 3. Base material layer (first base material layer)
[0164] 4 Adhesive layer (first adhesive layer)
[0165] 5 Barrier layer
[0166] 6 Adhesive layer (second adhesive layer)
[0167] 7. Base material layer (second base material layer)
[0168] 10 Stretch film
[0169] 11 Stretch film
[0170] 20-layer stack.
Claims
1. A stretched film comprising at least a first substrate layer and a barrier layer, characterized in that: The first substrate layer has a density of 0.950 g / cm 3 The above polyethylene is the main component, The barrier layer is mainly composed of ethylene-vinyl alcohol copolymer. Water vapor transmission rate is 3.5g / m 2 ·Day or less, The thermal shrinkage rate when heated at 100° C. for 10 minutes in the stretching direction of the film is 5% or less.
2. The stretched film according to claim 1, characterized in that: A first adhesive layer is disposed between the first substrate layer and the barrier layer.
3. The stretched film according to claim 2, characterized in that: The stretched film further comprises a second substrate layer, The second substrate layer has a density of 0.950 g / cm 3 The above polyethylene is the main component, A second adhesive layer is disposed between the barrier layer and the second substrate layer.
4. A method for producing a stretched film, characterized in that: The method for manufacturing a stretched film at least comprises the steps of preparing an original film and stretching the original film, wherein the original film at least comprises a film having a density of 0.950 g / cm 3 The above-mentioned base material layer with polyethylene as the main component and the barrier layer with ethylene-vinyl alcohol copolymer as the main component, The stretching temperature of the stretching treatment is 80° C. or higher and lower than 130° C., and the stretching ratio is 5 times or higher and 10 times or lower.
Citation Information
Patent Citations
Stretched film for laminate and laminate film
JP2021154656A
MDO multilayer polyethylene film
US20080178768A1
Recyclable, Easily Tearable Packaging Laminate Having A Good Barrier Effect And Method For Production Thereof
US20200122439A1